KADI ABDULCEBBAR’DA DÜŞÜNCE-BİLGİ İLİŞKİSİ - İbrahim Aslan (İslami İlimler Dergisi)
This article deals with Qadi Abd al-Jabbar’s approach to the relationship between thought and knowledge. In this framework, how thought and knowledge should be considered in the context of the ‘tawlîd’ theory is discussed. Besides this, epistemological concepts such as nazar, dalîl, madlûl, ta‘alluq, ma‘nâ, hâl, sukûn al-nafs, and i‘tiqâd are discussed from the point of their relations to each other. Abd al-Jabbâr searches for the definition and nature of “knowledge” as what can be called a “conceptional network” through his approach at issue.